Expression Levels of pvcrt-o and pvmdr-1 Are Associated with Chloroquine Resistance and Severe Plasmodium vivax Malaria in Patients of the Brazilian Amazon - Melo, Gisely C. (Public Library of Science, 2014)
Molecular markers associated with the increase of chloroquine resistance and disease severity in Plasmodium vivax are needed. The objective of this study was to evaluate the expression levels of pvcrt-o and pvmdr-1 genes in a group of patients presenting CQRPv and patients who developed severe complications triggered exclusively by P. vivax infection. Two different sets of patients were included to this comprehensive study performed in the Brazilian Amazon: 1) patients with clinically characterized chloroquine-resistant P. vivax compared with patients with susceptible parasites from in vivo studies and 2) patients with severe vivax malaria compared with patients without severity. Quantitative real-time PCR was performed to compare the transcript levels of two main transporters genes, P. vivax chloroquine resistance transporter (pvcrt-o) and the P. vivax multidrug resistance transporter (pvmdr-1). Twelve chloroquine resistant cases and other 15 isolates from susceptible cases were included in the first set of patients. For the second set, seven patients with P. vivax-attributed severe and 10 mild manifestations were included. Parasites from patients with chloroquine resistance presented up to 6.1 (95% CI: 3.8–14.3) and 2.4 (95% CI: 0.53–9.1) fold increase in pvcrt-o and pvmdr-1 expression levels, respectively, compared to the susceptible group. Parasites from the severe vivax group had a 2.9 (95% CI: 1.1–8.3) and 4.9 (95% CI: 2.3–18.8) fold increase in pvcrt-o and pvmdr-1 expression levels as compared to the control group with mild disease. These findings suggest that chloroquine resistance and clinical severity in P. vivax infections are strongly associated with increased expression levels of the pvcrt-o and pvmdr-1 genes likely involved in chloroquine resistance.